Effect of combination among vermicompost, salicylic acid and bacterial bioagents on management of Rhizoctonia crown and root-rot of strawberry - Ossama M. Badawy (Caspian Journal of Environmental Sciences)
Isolation from the roots of strawberry plants appearing mainly root-rot signs collected from Ismailia, Sharkia, Kalubia in addition to Giza governorates resulted in Macrophomina phaseolina, Fusarium oxysporum, Pythium ultimum (fungus-like), F. solani, Phytophthora cactorum (fungus-like), Rhizoctonia fragariae, Sclerotium rolfsii in addition to R. solani. Pathogenicity test of the isolates proved that they prompted root-rot signs as well. Both R. fragariae in addition to R. solani were the most malignant ones. Four isolates of Bacillus spp., i.e., Bacillus cerous, B. humilus, B. megaterium, B. subtils in addition to Pseudomonas fluorescens and P. putida were also isolated from the rhizospheric soil of strawberry plants cultivating in a field exhibiting a serious illness by root-rot. They were assessed for their inhibitory effect towards both R. fragariae and R. solani in vitro or in vivo. On the whole, P. fluorescens accompanied by Bacillus subtilis were the foremost efficacious in lowering the linear outgrowth of both pathogenic fungi. Sanitized aqueous filtrate of the examined vermicompost leaded to substantial drop in the linear outgrowth of the examined two fungi in comparison with untreated group. This drop was progressively raised by elevating its concentration. The combination among vermicomposting, salicylic acid (SA) or the bioagents B. subtilis or P. fluorescens leaded to substantial drop in strawberry root-rot with substantial elevation in the produced fruits in addition to their total soluble solids (TSS), either every of them was utilized only or in their diverse arrangements, in comparison to control treatment (infested with any of causative two fungi). On the opposite side, vermicompost was the most efficacious in this case in comparison with the remaining three illness management elements, i.e., SA in addition to the biologic agents B. subtilis or P. fluorescens when every of them was utilized only. Furthermore, no obvious infection was found when vermicompost, SA, the biologic agents B. subtilis or P. fluorescens, in addition to soil solarization were applied together. Then, the yielded fruits were obtained with a high TSS, firmness or total ascorbic acid (vitamin-c), to some extent, comparable to untreated group (un-infested soil with the any of causative fungi).